Oncogenic CMTM6 drives M2a macrophages formation and fuels cervical cancer progression - Yin, Bo; Chen, Chun; Huang, Baoyou; Ding, Jianyi; Hu, Haoran; Zhou, Huijuan; Zhu, Yashi; Huang, Tiefeng; He, Xiang; Lu, Yuan; Han, Lingfei (Frontiers in Immunology, 2025)
IntroductionCMTM6, a member of the CKLF like MARVEL transmembrane (CMTM) gene family, has emerged as a critical orchestrator of oncogenic processes, yet its specific role in cervical cancer (CC) remains insufficiently characterized. Mounting evidence implicates that CMTM6 in sculpting an immunosuppressive tumor microenvironment (TME).MethodsWe investigated the expression and functional role of CMTM6 in CC cells using in vitro biological assays and a mouse xenograft model. The impact of CMTM6 on macrophage polarization and its association with tumor progression were systematically evaluated through a series of in vitro and in vivo experiments, focusing on the induction of M2a macrophage polarization and activation of the mTOR signaling pathway.ResultsOur results demonstrate that exosomes secreted by CC cells encapsulate CMTM6, which is actively internalized by macrophages, inducing M2a polarization and triggering immunosuppressive pathways. Excessive macrophage infiltration in the TME, particularly in the presence of CMTM6, is strongly associated with unfavorable prognosis. Furthermore, exosomal CMTM6 activates the mTOR signaling pathway in tumor-associated macrophages, enhancing CCL2 secretion, which further promotes M2a polarization and accelerates tumor metastasis.DiscussionThese findings highlight exosomal CMTM6 as a crucial driver of immune suppression in CC, with the CMTM6/CD206/CCL2 axis significantly increasing the risk for CC patients. Our study underscores the potential of exosomal CMTM6 as both a prognostic biomarker and a therapeutic target for CC immunotherapy.